The benefits of HIV/AIDS intervention in the workplace: A case study - F. le R. Booysen; J. Molelekoa (South African Journal of Economic and Management Sciences, 2002)
Over the next ten years, as the AIDS epidemic takes its toll on the economically active population, employers will incur considerable costs. However, relatively inexpensive interventions, if implemented now, can yield substantial returns and save business considerable amounts of money. Thus, social responsibility can be argued to make economic sense. Worrying, though, is that there also appears to be a general apathy on the part of business, especially amongst small and medium-sized enterprises. A lot needs to be done to change the attitude of business and get business actively involved in the fight against HIV/AIDS. The private sector can and need to do its share in an integrated, coordinated response to HIV/AIDS, thus contributing to the initiatives on which the government, NGOs and communities have already embarked.